Preventive maintenance management: an approach towards a sustainability of adaptive re-use historical buildings in kuala Lumpur, Malaysia - Omar, Y.; Ishak, N.H. (2009)
The change to re-use and adaptation of buildings is a trend that has been clearly chartered in Malaysia. The importance of this trend is to extending the useful life of existing buildings supports the key concepts of sustainability. One of the reasons for the interest in adaptation is the growing perception that old buildings are often cheaper to convert to a new uses than to demolish and rebuild. It has been identified as having an important impact on sustainability of the built environment. The main purpose of this paper is to study and identify issues and problems in managing maintenance of adaptive re-use buildings. Perception on viability of adaptive re-use concept and the impact it has on the sustainability of existing built environment in Kuala Lumpur also will be addressed. The research was conducted based on responses from the case studies and structured questionnaire from a number of maintenance managers all of whom are responsible for significant of historic buildings within their portfolios. The finding revealed that adaptive re-use building’s maintenance management is carried out without referring to any proper conservation standard guidelines and neither properly planned. The related problems and ficient amount of financial support, inconsistent co-operation by the related parties who are unable to carry out the buildings control works. Recommendations are highlighted in solving identified issues and problems such aissues faced by building management teams on adaptive re-use buildings are enforcement of legal aspect, insufs strengthening the enforcement of conservation legislations and guidelines, systematic planned maintenance management, promote public awareness and enhance research and development related to adaptive re-use of historical buildings.